The Wiley handbook of what works in violence risk management theory, research and practice - Craig, Leam; Hogue, Todd E.; Wormith, J. S. (Hoboken, NJ Wiley Blackwell, 2020)
The magnitude and scope of human violence is vast and its manifestations take many forms. As such, it remains one of the terrible ills with which our species must contend. Arguably, it remains as complex and resistant to amelioration as fatal medical conditions such as cancer and "super bugs," chronic economic issues such as poverty, hunger, and homelessness, and political blights such as warfare, displaced refugees, and ethnic cleansing. Violence, by definition, always has an impact on individuals and often extends to the broader community and society as a whole. Consequently, society has a tremendous responsibility to address violence and to challenge both its causes and its perpetrators. However, the diversity of forms by which violence is enacted dictates that our range of responses must be equally diverse. Social sciences and their allied professions offer a number of important strategies to address violence by furthering theories of violence, generating empirical data about violence, and translating the resulting knowledge into policy and practice. But when it comes to violence, the devil is, quite literally, in the details"--
Includes bibliographical references and index.
Keywords: Violence; Violent crimes; Violent offenders